The Covid-19 impact on the mutual funds industry: a study on the pandemic effects on Latin American fund flows - Romanello, Leonardo Agulhon (2022)
The purpose of this paper is to look at the impact of the spread of the pandemic, in Latin American countries, on the mutual funds industry, through the lens of an especially designed COVID-19 Fear Index, which tracks the number of new deaths and new cases of coronavirus in each region. The main hypothesis is that the COVID-19 Fear Index is a statistically significant predictive factor of the net redemption of funds. The analysis was run for the year 2020, the outbreak of the Covid-19 pandemic. It was possible to conclude, after all, that the COVID-19 Fear Index was a statistically significant variable in several categories of mutual funds, across different countries. Overall, for the Balanced Funds category, the Fear Index had a negative coefficient, indicating that the increase in the number of deaths and/or new cases would decrease the investment flow in the given category. On the contrary, for the Fixed Income category, the index had a positive coefficient sign, which means that investors, in the scenarios where the pandemic was getting worse, moved their investments to less risky asset classes, such as fixed income funds, in lieu of balanced funds. All things considered, we hope that this study can shed some light on the possible repercussions of crisis situations – in this case, a sanitary one– on financial markets.